USER INTERFACE DISPLAY DESIGN TO ASSIST FOOD WASTE MANAGEMENT USING THE USER CENTERED DESIGN METHOD - Kamarulredzuan, Moch Baiz; Setiawan, Dadang; Sulistiyo Kusumo, Dana (Informatika, Universitas Jenderal Soedirman, 2024)
The designed user interface is mobile-based which aims to help manage food waste, especially for Bandung area students. The user interface display contains education about food waste, food waste banks and food donations. It is hoped that the user interface display created can help in managing food waste. Food waste in Indonesia is very concerning, for example in the city of Bandung there are 772.69 M3/day, which is 44.51% of the total of various types of food waste in 2021. Therefore a solution is needed that can help manage food waste. By utilizing technology, we can provide education about waste using a smartphone. Then a user interface display design is made using the user centered design method. The user centered design method is needed because it has an interface design process that focuses on usability goals. This method begins with collecting user information through questionnaires, then analyzing user information and obtaining user needs, then creating user flows, wireframes, mockups, and prototypes. After that, a usability test is carried out using the system usability scale method to see whether the user interface display that is made can meet user needs. The result of the system usability scale score is 87,5 and is in the excellent category, indicating that the user interface is good.